Letter from H. A. Straus to The Emergency Rescue Committee - Straus, H. A. (1940)
Hans A. Straus writes to the Emergency Rescue Committee on behalf of Dr. Alfred Reis (1882-1951), to request the Committee contact the President's Advisory Committee to access Reis' documentation for immigration.
Keywords: Bredig, Max Albert, 1902-1977; International Rescue Committee; Straus, H. A.; Reis, Alfred J., 1882-1951; Jewish refugees; Emigration and immigration